Population Genetics of Konosirus punctatus in Chinese Coastal Waters Inferred From Two mtDNA Genes (COI and Cytb) - Liu, Bingjian; Zhang, Kun; Zhu, Kehua; Shafi, Muhammad; Gong, Li; Jiang, Lihua; Liu, Liqin; Muhammad, Faiz; Lü, Zhenming (Frontiers in Marine Science, 2020)
Konosirus punctatus inhabits areas of significant commercial importance in Chinese coastal waters. Twelve populations distributed all along the Chinese coast were analyzed using two mtDNA genes. The cytochrome oxidase subunit I (COI) and cytochrome b (Cytb) genes were amplified from 242 and 259 individuals, respectively, and fragments of 999 and 415 bp sequence in length were used for analysis. COI and Cytb denoted a high haplotype diversity and low nucleotide diversity. The COI mtDNA gene revealed a high molecular variance within populations and low variance among populations, whereas Cytb showed a high variance among populations and low within populations. FST values obtained for COI and Cytb showed low genetic differentiation among the populations, except for the Zhongshan population where the Cytb gene showed high FST values. The constructed phylogenetic tree and haplotype network tree showed a single lineage, however, Cytb gene data showed that the Zhongshan population has a greater difference level within a population. The present investigation contributed to existing knowledge of the genetic structure of K. punctatus and can be useful for its future conservation.